Grazing in children: associations with child's characteristics and parental feeding practices - Conceição, Eva Martins (2020)
Purpose Grazing is a problematic eating behavior linked with poor weight loss outcomes, disordered eating psychopathology, and psychological distress in the adult population. However, no study assessed this behavior in children. Childhood is an important time frame for the development and maintenance of healthy eating habits, which can be influenced by children's psychological state, eating habits, and parental practices. This study investigates the associations between grazing behavior in children and children's psychological variables (anxiety, depression and withdrawn symptoms, body image dissatisfaction), children eating habits, and parental feeding practices. Methods In this cross-sectional study, 330 primary school students (6-10 years old) and their parents completed measures assessing children's grazing, anxiety/depression and withdrawn symptoms, body image dissatisfaction, children eating habits and style, and parental feeding practices. Results The path analysis tested showed that more restrictive parental feeding practices, inappropriate children eating habits, children's anxiety/depression symptoms, and body image dissatisfaction were associated with increased grazing scores (CMIN = 12.679; DF = 11; p = 0.315; RMSEA = 0.025; CFI = 0.990; NFI = 0.935; TLI = 0.982; IFI = 0.991; SRMR = 0.045). Conclusion Grazing tends to occur in a context of children's psychological distress, inappropriate children eating habits, and restrictive parental feeding practices. These variables should be addressed for the improvement of healthy eating habits and in weight-loss interventions for children.